Evaluasi Efektivitas Edukasi Gizi menggunakan Video Animasi terhadap Pemahaman Label Pangan pada Ibu Rumah Tangga di Kota Padang: Evaluating the Effectiveness of Animated Video Nutrition Education on Food Label Knowledge among Housewives in Padang City - Dewi, Risti Kurnia; Martfida, Rahmi; Satriya, Muhammad Agung (Universitas Airlangga, 2026)
Background: Unhealthy dietary patterns are one of the main contributors to the high prevalence of nutritional problems in Indonesia. This issue may stem from low nutrition literacy, including limited understanding of food labeling. Therefore, a nutrition education intervention is needed. It is not only to improve comprehension of food labels but also to promote healthier dietary behaviors. Objectives: This study aimed to evaluate the effectiveness of nutrition education using animated videos in improving food label comprehension among housewives in Padang City. Methods: A quasi-experimental design was employed to 90 housewives residing in Padang City. Respondents were then divided into control and intervention groups. The intervention group received nutrition education using animated videos on food labeling, which were delivered four times over four consecutive weeks. A paired t-test was conducted to assess pre- and post-intervention differences within each group. Results: The findings indicated an increase of 15.5 points in knowledge and 11.0 points in attitude scores within the intervention group. The T-test results showed a significant difference (p-value<0.001 and p-value<0.001) in both knowledge and attitude in the intervention group, while no significant differences were observed in the control group (p-value=0.160 and p-value =0.160). The N-gain scores were 81.15% for knowledge and 50.23% for attitude, suggesting that the video media was effective in improving knowledge, but less effective in enhancing respondents' attitudes toward food labeling. Conclusions: Nutrition education using animated video media proved to be effective in increasing knowledge and understanding, but was not yet effective in improving food labeling attitudes among housewives in Padang City.